The role of the private sector in providing foster care services for children without parental care in Malaysia - A. Kadir, Nadhilah; Mohd, Azizah (CFRU & IBT, 2021)
The paper deals with the role of private sector or non-governmental organisa-tion in providing welfare services to children without families through alternative care options. These children may include orphans as well as abandoned, abused and ne-glected children who basically have been deprived of parental care and family envi-ronment. According to the United Nations Convention on the Rights of the Child 1989, alternative care options may consist of foster placement, kafālah of Islamic law, adop-tion and institutional care. In this regard, this paper discusses the notion of each of the alternative care options which can be divided to institutional care and family based care. The paper also analyses in brief the relevant law and policy on family based care, namely, foster care and adoption in Malaysia such as the Child Act 2001, Adoption Act 1952 and Registration of Adoptions Act 1952. The paper further examines the role of private sector in providing relevant alternative care options for children without fam-ilies in Malaysia. The paper also highlights the role of private sector in arranging family based care for these children through foster care and adoption. For instance, there is cooperation between the government, Malaysian Social Welfare Department and a non-governmental organisation, OrphanCare, to place children from institutional care in foster care and adoption through deinstitutionalisation process. Finally, the paper investigates the challenges in encouraging private sector to arrange family based care for children without families through foster care and adoption. These challenges may include in raising awareness of the importance of family setting and inadequacy of the law and policy in providing alternative care for children without families. This study adopts a qualitative research method which is mainly based on library research. This paper found that family based care through foster care and adoption for children with-out families are preferred over institutional care. However, there are several issues that need to be addressed before institutionalised children can be effectively placed in foster care and adoption. Significantly, the private sector welfare plays an important role in the transition of these institutionalised children to a family setting.